“Working Capital Management” and “Corporate Governance and ESG” to analyze the effectiveness of financial resource management in the context of sustainable development and social responsibility of companies - Askerbek S. Zh.; Arystangaliyev A.M.; Shakir K. A.; Kupeshova B. K. (Research Retrieval and Academic Letters, 2024)
This article analyzes the impact of effective working capital management on the financial stability and growth of companies in the context of corporate governance principles and ESG aspects. Using the example of three Kazakhstani companies - Kazatomprom, Mangistaumunaigas and Zhaiykmunai - the financial indicators for the last three years were studied, as well as an analysis of the measures taken to manage working capital and comply with the principles of corporate governance and ESG. The results show that companies that successfully integrate ESG principles into their management strategy usually demonstrate more efficient use of working capital and higher financial stability. The authors identify the key factors of successful working capital management within the framework of corporate governance and ESG and offer practical recommendations for other companies seeking to improve their financial performance and comply with the principles of sustainable development and social responsibility.In modern business, working capital management is the main aspect of the financial management of the organization. Working capital is a set of funds necessary to ensure the operational activities of the company, including the purchase of raw materials and materials, the production, storage of finished products, the sale of goods and services. Working capital management is aimed at optimizing the turnover of assets and ensuring a sufficient level of liquidity for the smooth functioning of the business. In this introduction, consider the main aspects of working capital management, for example, the identification of its components, management methods and factors affecting the effectiveness of this process. Working capital management plays an important role in the financial health of the enterprise, affecting its ability to ensure current operations and growth. The main goal of working capital management is to optimize the relationship between the current assets and liabilities of the company in order to reduce the costs of storing assets and maximize cash flow. To do this, it is necessary to effectively manage inventory, receivables and payables, as well as assess the need for additional financing. In this introduction, we will consider the main strategies and tools for managing working capital, as well as their impact on the financial stability and competitiveness of the enterprise. The relevance of working capital management is manifested in the context of a modern dynamic economic environment in which companies face a number of difficulties and opportunities: 1.efficient use of resources: in the face of competition and market variability, companies should strive to make the most of their resources, including working capital. Working capital management allows you to optimize processes and reduce the costs of maintaining stocks, receivables and payables. 2.ensuring liquidity: effective working capital management allows companies to ensure a sufficient level of liquidity to cover current operations and liabilities. This is especially important during periods of temporary financial difficulties or market instability. 3.improve financial stability: proper working capital management contributes to improving the financial stability of the company, reducing its dependence on external financing and liquidity deficit risks. 4.investment optimization: working capital optimization allows companies to free up funds to invest in Business Development, Research and development of new products and services, which contributes to their competitiveness and growth in the market. All these factors indicate the importance of working capital management as the main aspect of the financial management of the enterprise in the modern economic environment.